(untitled) (Tanzania Medical Journal, 2020)
Background Malignancies are characterized by changes in the complete blood count. This study assessed the various derangements of complete blood count of female breast cancer patients when compared to controls, and their prognostic significance especially in relation to thrombosis using the Khorana Score. Methods This was a cross-sectional study. About 4.5mls of blood each was collected in an EDTA bottle from 45 breast cancer patients and 50 apparently normal controls in this cross- sectional study. Analysis was done on each sample on same day of collection on the Sysmex KN- 21N haemato- analyzer. Results In this study, 73.9% of the breast cancer patients had anaemia (Hb concentration < 12.5g/dl). The mean values of the Hb, PCV, RBC (11.26 ± 1.94 g/dl, 33.56 ±4.85%,4.14 ± 0.60) were significantly lower than the controls (12.67 ± 1.11 g/dl, 37.42 ± 3.08%,4.58 ± 0.42; p< 0.001, 0.001 and 0.002) respectively. Lymphocyte percentage and ALC were also significantly lower in the breast cancer patients. The mean values of the platelets, neutrophil percentage, NLR and PLR were significantly higher in the breast cancer patients. Only platelets and PLR were significantly positively correlated with tumour stage and size (Platelets. r= 0.448, p<0.002; r= 0.480 p<0.001. PLR r= 0.445, p<0.002; r=0.331, p<0.027). WBC and PLR were significant as a measure of disease progression across the stages of disease (p< 0.048 and 0.038 respectively), while platelets, WBC, and ANC were significant as a measure of tumour size (p < 0.005, 0.021 and 0.038 respectively). The Khorana Score showed that 2 (4.4%) of the patients were at a high risk of having a thrombosis. Conclusion Breast cancer patients have deranged CBC pattern when compared to normal controls, and with clinicopathologic significance including increased risk of thrombosis. Keywords: complete blood count, chemotherapy, cancer, haematological ratios, Khorana score.